Parent Perspectives on Short-Term Recovery After Spinal Fusion Surgery in Children With Neuromuscular Scoliosis. (December 2020) - Garrity, Brigid M; Singer, Sara J; Ward, Erin; Bastianelli, Lucia; Berry, Jay G; Crofton, Charis; Glader, Laurie; Casto, Elizabeth L; ,; Cox, Joanne E
Family perspectives on short-term recovery after spinal fusion for neuromuscular scoliosis are essential for improving patient outcomes. Semistructured interviews were conducted with 18 families of children within 3 months after spinal fusion performed August 2017 to January 2019 at a children's hospital. Interviews were recorded, transcribed, and coded line-by-line by 2 independent reviewers using grounded theory to identify themes. Five themes emerged among families when reflecting back on the postoperative recovery: (1) communicating and making shared decisions regarding postoperative care in a patient- and family-centered manner, (2) setting hospital discharge goals and being ready for discharge, (3) planning for transportation from hospital to home, (4) acquiring supports for caregiving at home after discharge, and (5) anticipating a long recovery at home. Important family perceptions were elicited about the recovery of children from spinal fusion for neuromuscular scoliosis that will inform better perioperative planning for clinicians, future patients, and their families.